The Bone Bridge for Tibial ACL Graft Fixation: A Biomechanical Analysis of Different Tibial Fixation Methods for ACL Reconstruction. Issue 1 (5th January 2023) - Peez, Christian; Greßmann, Marvin; Raschke, Michael J.; Glasbrenner, Johannes; Briese, Thorben; Frank, Andre; Herbst, Elmar; Kittl, Christoph
Background: The tibial fixation site is considered the weak link in anterior cruciate ligament (ACL) reconstruction, and conflicting results regarding the biomechanical properties of various fixation methods have been reported. Purpose: To examine knots tied over a bone bridge and its biomechanical properties as a suitable tibial fixation method in ACL reconstruction. Study Design: Controlled laboratory study. Methods: We divided 40 fresh-frozen porcine tibiae into 4 equal groups to evaluate flexor tendon grafts set with standard tibial fixation techniques: (1) bone bridge (BB group), (2) suspension button (SB group), (3) combined interference screw and bone bridge (IFS/BB group), and (4) combined interference screw and suspension button (IFS/SB group). Each construct was subjected to cyclic loading (1500 cycles, 50-250 N, 1 Hz) with a servohydraulic materials testing machine to measure elongation; load-to-failure testing (displacement rate: 25 mm/s) was then performed. Load to failure, stiffness, and yield load were compared between constructs using 1-way analysis of variance. Results: The hybrid fixation constructs (IFS/BB and IFS/SB groups) showed significantly better biomechanical properties than the isolated extracortical fixation constructs (BB and SB groups) ( P < .05 for all). There were no differences between the isolated extracortical fixation constructs or between the hybrid fixation constructs in elongation or load to failure; however, stiffness of the IFS/BB group was significantly higher than that of the IFS/SB group (175.3 ± 16.6 vs 144.9 ± 20.1 N/mm, respectively; P < .05). Stiffness between the SB and BB groups was not significantly different. Conclusion: Hybrid fixation had superior biomechanical performance compared with isolated extracortical fixation. However, tibial graft fixation using a bone bridge either as isolated extracortical fixation or combined with an interference screw for hybrid fixation showed equivalent biomechanical properties compared with suspension button–based graft fixation. Clinical Relevance: The clinical use of a bone bridge for tibial graft fixation could reduce the cost for ACL reconstruction and lower the rate of implant-associated issues.